The benefits of hosting the Olympics are nonexistent — no cities want to host them - Short, John Rennie (Insider, 2017)
It looks like a victory for the International Olympic Committee, as the result could be Olympic Games without the embarrassments of empty seats and foul water of Rio, the massive cost overruns of Sochi or the awkward political moments of Beijing.
Keywords: olympics; hosting games; olympic games; international business